2008
DOI: 10.1353/pla.2008.0023
|View full text |Cite
|
Sign up to set email alerts
|

Who Is Not Using the Library? A Comparison of Undergraduate Academic Disciplines and Library Use

Abstract: This study examines the differences in undergraduate library use by academic discipline at Oregon State University (OSU). In the winter of 2006, an online questionnaire about physical and virtual library use was distributed to 3,227 OSU undergraduates; 949 responses were received. Chi-square tests were used to distinguish differences between user groups. The results indicate that students in the Agricultural Sciences College use the physical library less than students in the Liberal Arts College, Health and Hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Arts and humanities students are not particularly heavy library users, as they have been found to be in earlier work (De Jager, 2002;Nackerud et al, 2013;Maughan, 1999); in fact, they are lower users than social scientists on most dimensions. Earlier research found computing and engineering students to be relatively low users of library resources (Kramer & Kramer, 1968;Bridges, 2008;Cox & Jantti, 2012;Nackerud et al, 2013), although Chrzastowski and Joseph (2006) found that graduate students from the physical sciences and engineering used online resources more than graduates in other disciplines. Again, our results show that although students from the computing and engineering discipline are low users (relative to the control group of social sciences), they are not particularly different from some other disciplines, such as arts, in this respect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Arts and humanities students are not particularly heavy library users, as they have been found to be in earlier work (De Jager, 2002;Nackerud et al, 2013;Maughan, 1999); in fact, they are lower users than social scientists on most dimensions. Earlier research found computing and engineering students to be relatively low users of library resources (Kramer & Kramer, 1968;Bridges, 2008;Cox & Jantti, 2012;Nackerud et al, 2013), although Chrzastowski and Joseph (2006) found that graduate students from the physical sciences and engineering used online resources more than graduates in other disciplines. Again, our results show that although students from the computing and engineering discipline are low users (relative to the control group of social sciences), they are not particularly different from some other disciplines, such as arts, in this respect.…”
Section: Discussionmentioning
confidence: 99%
“…Chrzastowski and Joseph (2006) use high-level categories in order to fit with their university's organisational structure, but Whitmire (2002) is forced to exclude the life scientists at her institution from her analysis, because the theoretical structure of the study does not allow for them. Studies have also looked at different groups of library users: undergraduates (Wells, 1996;Bridges, 2008;Cox & Jantti, 2012), postgraduates (Chrzastowski & Joseph, 2006), and researchers at all stages of their careers Bulger et al, 2011;Housewright et al, 2013;Tenopir & Volentine, 2012). Finally, they have adopted various definitions of what constitutes library use -from gate entries to e-resource usage, book borrowing to searching behaviours -to explore how different groups engage with the library and its services.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Sheeja (2010) conducted the study to examine the perception of undergraduate students of engineering faculty towards the digital library, and results revealed that almost all students use digital library and further results revealed the students preferred digital format. The study was conducted by Bridges (2008) to investigate the difference in undergraduate library use by academic discipline and results indicated that students of the Engineering College use the virtual library less than students from Liberal Arts College. Zang et al, (2005) in their study sought to answer three questions; 1) Would the level of domain knowledge significantly affect the user's search behavior?…”
Section: Review Of Literaturementioning
confidence: 99%
“…10 Bridges' 2007 study of the differences in library use among undergraduates of different disciplines found that, "Although engineering students did not statistically differ from their peers in their use of the physical library, they were significantly less likely to use the online library resources when compared with students from liberal arts." 11 Our anecdotal experience at NC State has been similar: faculty are more likely to use electronic resources but not the physical space, undergraduates and master's students are more likely to use the spaces but not the resources, and PhD students are more likely to take advantage of both. However, in every case, resources and spaces must be convenient to access.…”
Section: Engineers As a Unique User Communitymentioning
confidence: 95%